Chemoselective Intramolecular Formal Insertion Reaction of Rh–Nitrenes into an Amide Bond Over C−H Insertion. Issue 12 (5th February 2019) - Kono, Masato; Harada, Shingo; Nemoto, Tetsuhiro
Abstract: The past few decades have witnessed extensive efforts to disclose the unique reactivity of metal–nitrenes, because they could be a powerful synthetic tool for introducing the amine functionality into unactivated chemical bonds. The reactivity of metal–nitrenes, however, is currently mainly confined to aziridination (an insertion into a C=C bond) and C−H amination (an insertion into a C−H bond). Nitrene insertion into an amide C−N bond, however, has not been reported so far. In this work we have developed a rhodium‐catalyzed one‐nitrogen insertion into amide C−N and sulfonamide S−N bonds. Experimental and theoretical analyses based on density functional theory indicate that the formal amide insertion proceeds via a rhodium‐coordinated ammonium ylide formed between the nitrene and the amide nitrogen, followed by acyl group transfer concomitant with C−N bond cleavage. Mechanistic studies have allowed rationalization of the origin of the chemoselectivity observed between the C−H and amide insertion reactions. The methodology presented herein is the first example of an insertion of nitrene into amide bonds and provides facile access to unique diazacyclic systems with an N−N bond linkage. Abstract : Novel nitrene insertion . An intramolecular insertion reaction of Rh–nitrene into amide C−N and sulfonamide S−N bonds has been developed (see figure) via the unprecedented formation of an N + −N − ylide from the Rh–nitrene and the amide nitrogen. Experimental and theoretical analyses of the reaction mechanism have also been conducted and support the ylide pathway.